Determinan Resiliensi Keuangan pada UMKM di Indonesia: Peran Manajemen Modal Kerja, Perencanaan Keuangan, dan Alat Keuangan Digital - Soemarno Hidayatullah. S; Muhammad Husni; Anto Andreawan (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of working capital management, financial planning, and digital financial tools on the financial resilience of micro, small, and medium enterprises (MSMEs) in Indonesia. MSMEs play a strategic role in the national economy, but remain vulnerable to financial pressures due to limited liquidity, weak financial planning, and low utilization of digital financial technology. This study used a quantitative approach with an explanatory survey design. Primary data were collected through questionnaires distributed to MSMEs using a purposive sampling technique, then analyzed using multiple linear regression to test the partial and simultaneous effects between variables. The results show that working capital management and financial planning have a positive and significant effect on MSME financial resilience. Digital financial tools also have a positive and significant effect and are the most dominant variable. Simultaneously, these three variables contribute significantly to improving MSME financial resilience. These findings confirm that strengthening MSME financial resilience requires effective working capital management, structured financial planning, and optimal utilization of digital financial technology.